EMERGING BUSINESS MODELS: BIBLIOMETRIC MAPPING OF CORE TRENDS (REMUNOM, 2026)
The sustainable transition has required organizations to reconfigure or create innovative business models aligned with social, economic, and environmental issues. In this context, the study aimed to map emerging business models in the academic literature, identifying economic trends and analyzing how they align with organizational strategies to create value and ensure adaptation to the market. The search adopted a bibliometric approach in the Web of Science and Scopus search databases, selecting 445 scientific articles published by 2023. Data processing was conducted using VOSviewer software and the Bibliometrix package in R environment. Additionally, a qualitative analysis based on the content analysis technique was applied to classify corporate strategies aimed at value creation. The mapping of co(occurrence) of keywords highlighted central themes such as sustainability, circular economy, innovation in business models and digital transformation. Among the most frequent trends, the Circular Economy, the Internet of Things (IoT), the Sharing Economy, and the Collaborative Economy stand out. The qualitative analysis showed that the association of emerging technologies and sustainable practices is a determining factor for the competitive evolution of organizations. It is concluded that currently, the competitiveness of companies depends on the incorporation of sustainable and technological models that optimize operational efficiency and meet the demands of conscious consumers. It is suggested that future research focuses on investigations on the effectiveness of these strategies in different sectors and deepens the study of trends that are still little explored in the field of weconomy.